The Use Virtual Trading Simulation in Teaching Stock Market: A Quasi-Experimental Method - Satrio Wijoyo; Endang Supardi; Komang Ade Komala Savitri; Mutiah Mutiara Firdaus (Didaktika: Jurnal Kependidikan, 2024)
This study explores the effectiveness of virtual stock trading simulations in enhancing financial literacy among high school students. A quasi-experimental design was used, involving 61 students (29 male and 32 female) from SMAIT As-Syifa Boarding School Wanareja, Subang. The students participated in virtual trading simulations via the Stockbit platform, with financial literacy measured through pre- and post-tests. The results showed significant improvements in both groups, with male students’ post-test scores rising from 9.28 to 13.21 and female students’ from 8.97 to 11.13. Paired t-tests confirmed that these gains were statistically significant (p < 0.001). The findings indicate that virtual simulations are an effective tool for teaching stock market concepts, investment strategies, and financial decision-making. The study underscores the value of integrating technology into educational curricula to bridge the gap between theoretical knowledge and practical financial skills. However, limitations such as the study's sample size and focus on short-term outcomes suggest the need for further research in more diverse educational settings and on long-term learning effects.